DNA replication in eukaryotic cells - DePamphilis, Melvin L (Cold Spring Harbor Laboratory Press, 1996)
National Institutes of Health. Extensive text on the replication of DNA, specifically in eukaryotic cells, for researchers. 68 contributors, 54 U.S.
Cold spring harbor monograph series ; Monograph 31
Keywords: biochemie; biologie; eukaryotické buňky; DNA; Eukaryotic Cells